Peningkatan Kemampuan Menyimak Berita Dengan Menggunakan Metode Team Product - Nur Hafsah Yunus (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Al Asyariah Mandar, 2018)
This study aims to: (1) To find out the implementation of learning to listen to news using Team Product method on class VIII students SMP Negeri 3 Malunda; (2) To find out how the team product method can improve the ability to listen to the news of the students of class VIII SMP Negeri 3 Malunda. The population as the object of this research is class VIII SMPN 3 Malunda, Malunda Sub-district, Majene Tengah Regency for the academic year 2017 / 2018.The total number of students of class VIIID is 32 students, but the subject in this study only 30 students, sample in this study. Instruments used in this study there are two kinds of news capabilities and tests test questionnaire. The ability test is used to know the ability of the students to use the team product method to improve the ability to listen to the news, while the questionnaire used as data collection to determine the factors that influence the use of team product method to improve the ability to listen to news. The results of this study show the use of team product method to improve the ability of listening news is not sufficient, because the sample did not achieve results in accordance with predefined criteria. Factors affecting the ability of the students through the use of team product methods to improve the ability to listen to news are: Factors phsikologi learners, media limitations and facilities of instruction, environmental factors. From the results of the above analysis can be concluded that the level of use of team product methods in improving the ability to listen to news students in grade VIII SMPN 4 Malunda, Malunda District, Majene District has not been adequate.